Pengembangan Evaluasi Teknik Non Tes - Ahmad Anshari; Muhammad Zuhdi Hibatullah; Eka Widyanti (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The teaching and learning process is the core of education with teachers and learners playing the main roles. Evaluation is a key aspect of the educational process, ensuring the achievement of curriculum objectives. Evaluation not only measures student learning outcomes, but also helps understand the learning process and provides information for further improvement. Evaluation can be either test or non-test, and the use of both methods depends on the purpose of the assessment and the aspects of learning to be assessed. This research uses a literature review to explore the concepts and methods of non-test evaluation in education. Non-test evaluation includes various techniques such as performance assessment, project/product assessment, attitude assessment and others. The development of non-test evaluation is important as it allows for a comprehensive assessment of students' affective and psychomotor aspects, which cannot always be measured by written tests. The functions of non-test evaluation in education include measuring affective and psychomotor aspects, providing a holistic picture of students' abilities, supporting individualized learning, motivating students, and identifying strengths and weaknesses in learning. As such, non-test evaluation is an integral component of the learning process that helps maximize overall educational outcomes.